Waste cellulose extraction and analysis decortication sisal plant (Agave sisalana) Sumbawa Labangka - Widyawati, Fauzi; Malik Fajar Fatoni; Emsal Yanuar; Hidayat, Syamsul (Jurnal Pijar Mipa, 2023)
Waste utilization of decortication Sisal plants is minimal compared to the amount of waste produced, especially the cellulose content in the waste decortication sisal plant. This research aims to extract waste cellulose decortication sisal plants using acid and alkaline solutions with variations in NaOH solutions of 0%, 2%, 4%, 6%, and 8%. The process used is alkalization, bleaching, and acid hydrolysis by method analysis. Next, testing using SEM and FTIR methods is done to determine the morphology of waste cellulose decortication in the resulting sisal plants and the cellulose, lignin, and hemicellulose content in the waste decortication sisal plant. Before treatment, the cellulose content of the waste is given to decorticate the sisal plant at 31%, and after alkalization treatment, the cellulose content is 54%. Cellulose content in waste decortication Sisal plants in each process increases with found O-H bonds at waves 3000-3600 cm-1, C-H bonds belong to hemicellulose at wave numbers 2800-3000 cm-1 and remove lignin, which is in the waste decortication Sisal plants did not find C=C bonds belonging to lignin at waves of 1200-1300 cm-1. FTIR test results show an increase in cellulose intensity, with the resulting cellulose measuring 28.64762 µm and 33.69369 µm. The increase in cellulose intensity in FTIR is directly proportional to the SEM results, which show a loose layer with lignin and hemicellulose that has been eroded from the cellulose.